Effect of jaw clenching on balance recovery: dynamic stability and lower extremity joint kinematics after forward loss of balance - Ringhof, Steffen; Stein, Thorsten; Hellmann, Daniel; Schindler, Hans J. (Frontiers in psychology, 2016)
Postural control is crucial for most tasks of daily living, delineating postural orientation and balance, with its main goal of fall prevention. Nevertheless, falls are common events and have been associated with deficits in muscle strength and dynamic stability. Recent studies reported on improvements in rate of force development and static postural control evoked by jaw clenching activities, potentially induced by facilitation of human motor system excitability. However, there are no studies describing the effects on dynamic stability. The present study, therefore, aimed investigated the effects of submaximum jaw clenching on recovery behavior from forward loss of balance. Participants were twelve healthy young adults, who were instructed to recover balance from a simulated forward fall by taking a single step while either biting at a submaximum force or keeping the mandible at rest. Bite forces were measured by means of hydrostatic splints, whereas a 3D motion capture system was used to analyze spatiotemporal parameters and joint angles, respectively. Additionally, dynamic stability was quantified by the extrapolated CoM concept, designed to determine postural stability in dynamic situations. Paired t-tests revealed that submaximum biting did not significantly influence recovery behavior with respect to any variable under investigation. Therefore, reductions in postural sway evoked by submaximum biting are obviously not transferable to dynamic stability. It is suggested that these contradictions are the result of different motor demands associated with the abovementioned tasks. Furthermore, floor effects and the sample size might be discussed as potential reasons for the absence of significances. Notwithstanding this, the present study also revealed that bite forces under both conditions significantly increased from subjects’ release to touchdown of the recovery limb. Clenching the jaw, hence, seems to be part of a common physiological repertoire used to improve motor performance.
Gesehen am 21.10.2021